A systematic comparison of hepatobiliary adverse drug reactions in FDA and EMA drug labeling reveals discrepancies. Issue 1 (January 2022) - Wu, Yue; Xiao, Wenzhong; Tong, Weida; Borlak, Jürgen; Chen, Minjun
Highlights: Systematic comparison of 549 medications was conducted between FDA and EMA labeling. Our analysis found limited discrepancies in hepatic safety information. The discrepancies were mainly associated with non-severe or low-frequency hepatic adverse events. Abstract : Drug labeling informs physicians and patients on the safe and effective use of medication. However, recent studies suggested discrepancies in labeling of the same drug between different regulatory agencies. Here, we evaluated the hepatic safety information in labeling for 549 medications approved by the US Food and Drug Administration (FDA) and the European Medicines Agency (EMA). Limited discrepancies were found regarding risk for hepatic adverse drug reactions (ADRs) (8.7% in hepatic ADR warnings and 21.3% in contraindication for liver disease), while caution should be exercised over drugs with inconsistencies in contraindications for liver disease and evidence for hepatotoxicity (4.9%). Most discrepancies were attributable to less-severe hepatic events and low-frequency hepatic ADR reports and had limited implication on clinical outcomes.